How Go-Food by GOJEK Apps work on consumer purchase decisions - Entas, Derinta; Putri, Ni Made Dwiyana Rasuma; Widiastiti, A. A. Istri Putra; Hanum, Fauziah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Go-Food by GOJEK Apps is a popular food delivery platform in Indonesia. The main objective of this study is to understand the factors influencing consumer purchase decisions through the Go-Food by GOJEK Apps, such as delivery reliability, menu variety, food quality, price, and service quality. Methods of research are using a quantitative approach by collecting data through a survey using a questionnaire that has been developed. The research sample was taken randomly from the consumer population using the Go-Food by GOJEK Apps. The collected data were analyzed using descriptive statistical analysis and multiple linear regression. The results of the study show that delivery reliability, menu variety, food quality, price and service quality have a significant effect on consumer purchase decisions through the Go-Food by GOJEK Apps. Results of the research show that consumers tend to choose apps that offer fast delivery, a wide menu selection, high-quality food, competitive prices, and responsive service. These findings provide a better understanding of the factors influencing consumer purchase decisions through the Go-Food by GOJEK Apps. This research implies the importance of Go-Food service providers paying attention to these factors in improving user experience and consumer satisfaction. By understanding consumer preferences and needs, service providers can improve service quality, optimize delivery, provide interesting menu variations, and set prices accordingly.